Risalatul Mahid dan Relevansinya Pada Anak Usia Aqil Baliqh - Rizka Amalia; Uswatun Hasanah (Al-Mudarris, 2019)
This study examines the material Fiqhun Al-nisa' in the book Risalatul mahid and the values of education that are taught and need to be known by children of the age of' aqil baligh. The purpose of this study is that children are better able to understand and be able to apply the laws that have been taught in the Risalatul Mahid material and provide additional material that has not been discussed in the content of Fiqh in the school curriculum. This research is a case study with a descriptive qualitative approach conducted at MI Ma'arif Ngrupit Jenang Ponorogo. Data collection techniques from this study were nonparticipant observation, interviews and documentation in the form of taking photos during the learning process of risalatul mahid material in fiqh classes for women I and II. The results showed that the fiqhun nisa material in the classic book risalatul mahid by Abdul Hakim Muhammad As-samaroni has three main chapters namely the menstrual chapter, istihadloh and the postpartum chapter. With this specific material that is taught in the fiqh classes of women I and II, especially for children aged ‘aqil baligh as provisions and knowledge to be applied in their daily lives.